(untitled) (Iranian Journal of Kidney Diseases, 2011)
Severe hyperuricemia accompanied by the other comorbidities such as anuria, fluid overload, calcium-phosphate imbalance, and/or tumor lysis syndrome is one of the indications for dialysis in the setting of acute kidney injury. Rasburicase is used in different clinical conditions such as tumor lysis syndrome and uric acid nephropathy. Among referred patients to our center from 2008 to 2010, there were 3 patients who had an indication for dialysis because of hyperuricemia. Contributing factors to the acute kidney injury were multi-organ dysfunction, rapidly progressive glomerulonephritis, and spontaneous tumor lysis syndrome. None of the patients showed any response to treatment with bicarbonate and hydration. After rasburicase administration, serum uric acid level declined, and urine output increased. Treatment with a single low dose of rasburicase would be effective to decrease the serum uric acid level and reverse kidney injury secondary to uric acid nephropathy.